2020
DOI: 10.1007/s11467-020-0956-6
|View full text |Cite
|
Sign up to set email alerts
|

A new approach to solar flare prediction

Abstract: All three components of the current density are required to compute the heating rate due to free magnetic energy dissipation. Here we present a first test of a new model developed to determine if the times of increases in the resistive heating rate in active region (AR) photospheres are correlated with the subsequent occurrence of M and X flares in the corona. A data driven, 3 D, non-force-free magnetohydrodynamic model restricted to the near-photospheric region is used to compute time series of the complete c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 85 publications
0
5
0
Order By: Relevance
“…For example, modern flare and CME forecast models now often rely on combinations of magnetograms and sometimes images to assess the likelihood of a major x-ray outburst and/or a material eruption (e.g. Falconer et al, 2011;Goodman et al, 2020;Leka, Barnes, and Wagner, 2018;Leka et al, 2019). These approaches now can routinely make use of HMI images of active region vector fields combined with chromospheric magnetic field observations and related modeling to reconstruct the field geometry (e.g.…”
Section: Modeling: Space Weather Research and Operationsmentioning
confidence: 99%
“…For example, modern flare and CME forecast models now often rely on combinations of magnetograms and sometimes images to assess the likelihood of a major x-ray outburst and/or a material eruption (e.g. Falconer et al, 2011;Goodman et al, 2020;Leka, Barnes, and Wagner, 2018;Leka et al, 2019). These approaches now can routinely make use of HMI images of active region vector fields combined with chromospheric magnetic field observations and related modeling to reconstruct the field geometry (e.g.…”
Section: Modeling: Space Weather Research and Operationsmentioning
confidence: 99%
“…Among the flare prediction tools that do not use ML, Shramko et al (2019) demonstrated the possibility of forecasting flares within 24 hours relying solely on microwave radiation signatures. Goodman et al (2020) studied 14 active regions and showed that increases in the photospheric resistive heating rate in active regions are correlated with the occurrence of M and X flares a few hours to a few days later. Morales & Santos (2020) investigated the predicting capabilities of the Lu and Hamilton self-organised-criticality avalanche model (Lu & Hamilton 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the literature is rich in flareprediction methods applied to a wide range of observations of ARs (see, e.g. McCloskey et al 2018;Leka et al 2018;Campi et al 2019;Falco et al 2019;Goodman et al 2020;Lin et al 2020), as well as a number of studies devoted to the comparison between different prediction methods (see, e.g., Barnes et al 2016;Leka et al 2019a,b;Park et al 2020, and references therein).…”
Section: Introductionmentioning
confidence: 99%